Comparison between regression and ANN models for relationship of soil properties and electrical resistivity - Siddiqui, F.I. (Springer Verlag, 2015)
Precise determination of engineering properties of soil is essential for proper design and successful construction of any structure. The conventional methods for determination of engineering properties are invasive, costly, and time-consuming. Geoelectrical survey is a very attractive tool for delineating subsurface properties without soil disturbance. Proper correlations of various soil parameters with electrical resistivity of soil will bridge the gap between geotechnical and geophysical engineering and also enable geotechnical engineers to estimate geotechnical parameters from electrical resistivity data. The regression models of relationship between electrical resistivity and various soil properties used in the current research for the purpose of comparison with artificial neural network (ANN) models were adopted from the work of Siddiqui and Osman (Environ Earth Sci 70:259â26, 2013). In order to obtain better relationships, ANN modeling was done using same data as regression analysis. The neural network models were trained using single input (electrical resistivity) and single output (i.e., moisture content, plasticity index, and friction angle). Twenty (20) multilayer feedforward (MLFF) networks were developed for each properties, ten (10) each for two different learning algorithms, Levenberg-Marquardt (LM) and scaled conjugate gradient (SCG). The numbers of neurons in hidden layer were experimented from 1 to 10. Best network with particular learning algorithm and optimum number of neuron in hidden layer presenting lowest root mean square error (RMSE) was selected for prediction of various soil properties. ANN models show better prediction results for all soil properties. Â© 2014, Saudi Society for Geosciences.